Extending the discussion on inconsistency in forensic decisions and results - Buckleton, John; Bright, Jo‐Anne; Taylor, Duncan; Curran, James; Kalafut, Tim (Journal of forensic sciences, 2024)
The subject of inter‐ and intra‐laboratory inconsistency was recently raised in a commentary by Itiel Dror. We re‐visit an inter‐laboratory trial, with which some of the authors of this current discussion were associated, to diagnose the causes of any differences in the likelihood ratios (LRs) assigned using probabilistic genotyping software. Some of the variation was due to different decisions that would be made on a case‐by‐case basis, some due to laboratory policy and would hence differ between laboratories, and the final and smallest part was the run‐to‐run difference caused by the Monte Carlo aspect of the software used. However, the net variation in LRs was considerable. We believe that most laboratories will self‐diagnose the cause of their difference from the majority answer and in some, but not all instances will take corrective action. An inter‐laboratory exercise consisting of raw data files for relatively straightforward mixtures, such as two mixtures of three or four persons, would allow laboratories to calibrate their procedures and findings.